A review on flow boiling enhancement and fabrication of enhanced microchannels of microchannel heat sinks. (August 2021) - Deng, Daxiang; Zeng, Long; Sun, Wei
Manuscript's Highlights: Recent advancements in enhanced microchannels and their fabrication methods are reviewed Four types of enhanced microchannels and their enhancement performance have been identified Typical fabrication methods for enhanced microchannels has been discussed Insights and recommendations on future directions of enhanced microchannels have been proposed Abstract: Rapid increase in heat fluxes within a small area in microelectronic, defense, energy, solar and medical components has spurred an urgent need for two-phase microchannel heat sinks due to their large heat transfer area to volume ratios, compact heat sink size, and high heat transfer coefficient (HTC). Nevertheless, underlying problems of large wall superheat for onset of nucleate boiling, inherent flow instability and low values of critical heat flux of flow boiling in conventional solid parallel microchannels pose severe challenges for practical applications of microchannel heat sinks in high heat flux dissipations. To address the above issue, numerous efforts have been taken to the design and fabrication of enhanced microchannels for flow boiling enhancement of two-phase microchannel heat sinks in recent years. To overview this subject, recent advancements in flow boiling enhancement and fabrication of enhanced microchannels are comprehensively reviewed in this paper. To the best knowledge of the authors', it is the first time to present the advancements of enhanced microchannels from the fabrication perspective, which is critical for the application and commercialization of enhanced microchannel heat sinks. The enhanced microchannels are classified into flow disruption structures, reentrant cavity structures, porous structures, and nanostructures. Emphasis is on the flow boiling enhancement performance of these enhanced microchannels in microchannel heat sinks. Subsequently, typical fabrication methods for enhanced microchannels are summarized together with the discussion of their advantages and disadvantages, such as etching, micro-mechanical cutting, micro electrical discharge machining, laser processing, sintering, chemical vapor deposition and 3D printing. Finally, the challenges and future research directions of enhanced microchannels are reasonably clarified.